Characteristics of the consumer preferences research process - Mirela-Cristina Voicu (Global Economic Observer)
Information is one of the most important resources that a company must possess. Some information is hidden deep in the black box - the mind of the consumer, as in the case of information about consumer preferences. Although it seems a concept difficult to grasp, it was shown that consumer preferences can be effectively measured and their research may provide a deeper understanding of the choices that consumers make when deciding to select an offer against another and when deciding to continue in time the relationship with one supplier. The following paper reveals some important aspects regarding the use of information regarding consumer preferences, the fundamentals behind consumer preferences research and the milestones in the consumer preferences research process.